An exploration of the digital library evaluation literature based on an ontological representation. Issue 9 (19th July 2013) - Tsakonas, Giannis; Mitrelis, Angelos; Papachristopoulos, Leonidas; Papatheodorou, Christos
<x xml:space="preserve">Abstract</x> Evaluation is a vital research area in the digital library domain, demonstrating a growing literature in conference and journal articles. We explore the directions and the evolution of evaluation research for the period 2001–2011 by studying the evaluation initiatives presented at 2 main conferences of the digital library domain, namely the Association for Computing Machinery and the Institute of Electrical and Electronics Engineers (ACM/IEEE) Joint Conference on Digital Libraries (JCDL), and the European Conference on Digital Libraries (ECDL; since 2011 renamed to the International Conference on Theory and Practice of Digital Libraries [TPDL]). The literature is annotated using a domain ontology, named DiLEO, which defines explicitly the main concepts of the digital library evaluation domain and their correlations. The ontology instances constitute a semantic network that enables the uniform and formal representation of the critical evaluation constructs in both conferences, untangles their associations, and supports the study of their evolution. We discuss interesting patterns in the evaluation practices as well as in the research foci of the 2 venues, and outline current research trends and areas for further research.